(untitled) (Khairulummah, 2022)
Asad Mohammad Khan is a well know fiction writer, as well as an excellent translator His translated poems and fictions have published in various journals from time to time. He has translated many famous poems of the famous English poet Ezra Pound and received praise from critics. Apart from this, he has also translated many poems of Różewicz. He has maintained special care of literature in his translations and brought the translation to the level of creativity with his best additions. All his translations follow the rules of translation. At the same time, they highlight its meaning by adding and modifying it. According to his mood and taste, he selects for translation only those poems, which he can go deep into and understand with complete familiarity. He embellishes the translations with his charming style to be very close to the original and sometimes the reader gets the impression of the original poem. Apart from English, he has also translated classics of other languages. As a poet, he has always translated fluently without any semantic or linguistic hiccups and has made a name for himself in the field of translation. Therefore, Asad Muhammad is crowned as a successful and best translator in Urdu.